2022
DOI: 10.1111/liv.15320
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of liver cancer patients with SARS‐CoV‐2 infection: An International, Multicentre, Cohort Study

Abstract: Background & Aims: Information about the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients with liver cancer is lacking. This study characterizes the outcomes and mortality risk in this population.Methods: Multicentre retrospective, cross-sectional, international study of liver cancer patients with SARS-CoV-2 infection registered between February and December 2020. Clinical data at SARS-CoV-2 diagnosis and outcomes were registered.Results: Two hundred fifty patients from 38 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Cancer patients have a higher risk of SARS-CoV-2 infection and a worse prognosis than noncancer patients, and patients with high-risk tumors, especially those with an NRS2002 score ≥ 3 and advanced tumor stages, may have higher mortality [126] , [127] . The risk of death in cancer patients infected with COVID-19 is mainly influenced by age, sex and comorbidities and is independent of whether they have had radiotherapy, targeted therapy, immunotherapy, or hormonal therapy within the past 4 weeks [128] .…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer patients have a higher risk of SARS-CoV-2 infection and a worse prognosis than noncancer patients, and patients with high-risk tumors, especially those with an NRS2002 score ≥ 3 and advanced tumor stages, may have higher mortality [126] , [127] . The risk of death in cancer patients infected with COVID-19 is mainly influenced by age, sex and comorbidities and is independent of whether they have had radiotherapy, targeted therapy, immunotherapy, or hormonal therapy within the past 4 weeks [128] .…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
“…However, the trial had a small number of patients with HCC. In a large study of liver cancer patients infected with SARS-CoV-2, 52 patients died within 30 days of infection, and 43 (82.7%) of these deaths were related to SARS-CoV-2 infection [127] . In a follow-up study of patients with HCC, the COVID-19 pandemic led to a longer follow-up interval for patients, which may reduce the overall response rate of patients, and the prognosis of patients was worse when the follow-up interval was >95 days [129] .…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Although data are not univocal[ 25 ], several studies include the presence of HCC among the independent predictors of COVID-19-related mortality[ 15 , 30 , 38 ]. Among patients with CLD and COVID-19, HCC patients had 3.31 times the hazard of death for all causes, regardless of the presence of liver cirrhosis[ 30 ].…”
Section: Liver Cirrhosis and Covid-19 Clinical Outcomesmentioning
confidence: 99%
“…Several studies reported a significant decrease in the number of new HCCs diagnosed (up to 37%) during the pandemic, which is in marked contrast to the steady increases in previous years and suggests that incident cases went undiagnosed during this period [ 168 , 169 ]. In addition, HCCs diagnosed following the COVID-19 outbreak were significantly larger and more frequently associated with lymphadenopathy and extrahepatic disease, with a consequent shift toward a higher tumor burden at diagnosis.…”
Section: Covid-19 In Patients With Pre-existing Chronic Liver Diseasementioning
confidence: 99%